2022
DOI: 10.3389/fbioe.2022.805176
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytics for Influenza Virus-Like Particle Characterization and Process Monitoring

Abstract: Virus-like particles (VLPs) are excellent platforms for the development of influenza vaccine candidates. Nonetheless, their characterization is challenging due to VLPs’ unique biophysical and biochemical properties. To cope with such complexity, multiple analytical techniques have been developed to date (e.g., single-particle analysis, thermal stability, or quantification assays), most of which are rarely used or have been successfully demonstrated for being applicable for virus particle characterization. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, the charge state of the viral surface can influence the immune system's response to the virus and the binding of antibodies. 96,97 Nanoparticles can often expand the application of nanotechnology in medicine and biology by drawing on the functional and design principles of viral surface charge, which can optimize the properties of nanoparticles for cellular uptake, drug delivery and immune interactions. 98,99 Cui et al proposed a charge-reversible virus-mimicking nanocapsule for the effective systemic treatment of retractable gliomas.…”
Section: Mimicking Viral Physical Propertiesmentioning
confidence: 99%
“…In addition, the charge state of the viral surface can influence the immune system's response to the virus and the binding of antibodies. 96,97 Nanoparticles can often expand the application of nanotechnology in medicine and biology by drawing on the functional and design principles of viral surface charge, which can optimize the properties of nanoparticles for cellular uptake, drug delivery and immune interactions. 98,99 Cui et al proposed a charge-reversible virus-mimicking nanocapsule for the effective systemic treatment of retractable gliomas.…”
Section: Mimicking Viral Physical Propertiesmentioning
confidence: 99%
“…Another study also observed that a mutation in the capsid protein of the Sindbis virus can affect aggregation ( Ferreira et al, 2003 ). Detailed study of viral aggregates, for instance, using electron microscopy, nanoparticle tracking analysis, flow virometry, or tunable resistive pulse sensing, can be beneficial for characterizing viral aggregation in terms of size distribution, morphology, surface charge, composition, structure, and stability ( Heider and Metzner, 2014 ; Zamora and Aguilar, 2018 ; Carvalho et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…LNPs not only enhance the stability of the viral mRNA but also act as adjuvants [55,56]. Virus-like particles (VLPs) are also considered nanomaterials because of their size (10-200 nm) [57]. These are successfully used to deliver multiple antigens as vaccines [58,59].…”
Section: Discussionmentioning
confidence: 99%